ANALISIS HUKUM ISLAM TERHADAP PENERAPAN TARIF SURGE PRICING PADA SEWA TAKSI ONLINE UBER DI WILAYAH SURABAYA - Febriani Rokhmawati (Maliyah : Jurnal Hukum Bisnis Islam, 2018)
This research data collected through observation and interview then analyzed by using qualitative description method. This study uses a deductive mindset, which begins by presenting common notions, theories, or facts, namely the provisions of Islamic law concerning Ijarah and Upah in Islamic law which are further described from the fact that there is in the field the practice of applying surge pricing tariff on Uber's online taxi rental in Surabaya area, then researched and analyzed. The result of the research concludes that the application of surge pricing tariff applied by Uber during the rush hour using the principle of supply and demand economy, where if demand is high while inventory is insufficient then the cost of automatic travel increases. In the application of travel costs will increase between 1.1x - 5.5x fold. This happens suddenly and makes passengers pay a higher cost than regular travel, and this also only happens in certain areas and only takes a few minutes or hours. In Islamic law this application is actually permissible, but must be applied fairly, clearly, transparently and see the willingness of passengers with drivers. Uber also enforces the standard agreement contained in the uber manual which explains little about this surge pricing tariff, so with this standard agreement Uber is correct in applying the surge pricing tariff.